ARRANGEMENT OF REGIONAL REGULATION CONTENT MATERIAL AS THE NATIONAL LEGAL SUB-SYSTEM - M. Isa, Jalaluddin (Tadulako University, 2019)
Arrangement of the content material of regional regulation as part of the legislations sub-system adjustment in Indonesia must be directed in tone with the direction of national law development. In accordance with the National Long-Term Development Plan (RPJPN, 2005-2025), the development of national law is directed at the realization of a solid national legal system based on the Pancasila and the 1945 Constitution of the Republic of Indonesia which includes the development of legal material, legal structures, legal culture legal apparatus, legal facilities and infrastructure that can guarantee order, legal certainty, justice, truth and protection of human rights.The discussion in this article aims to raise a number of important relevant issues to be used as material for evaluation in structuring the content of the regional regulations as a sub-system of national law.The research method used in this study is legal research using a legislative approach and a conceptual approach.It is concluded that the regulation of the content material of the regional regulation as a sub-system of national law is not only placed in the legal sense as a mere system of order, thus creating a relationship of tension between the central government and the regional government, it but must be placed in a legal sense as a fluid relationship so that the determination of the content of the regional regulation is also fluid, for the good of the community and the government as a whole.